Modeling, Simulation, and Dynamic Analysis of Earth-Fault Detection in High-Voltage Transmission Networks - Nazif, D. M.; Bal, Yakubu Barau; Muhammad, Fatima; Umar, Sadik; Abdulrahman, Aliyu (Mikailalsys Journal of Advanced Engineering International, 2025)
This paper addresses the need for accurate and timely single-line-to-ground (SLG) fault detection in high-voltage transmission systems, particularly to improve grid reliability in developing regions. The research objective is to propose and validate an integrated framework that combines modeling, simulation, and real-time implementation for SLG fault identification and location. Methodologically, a dual-unit detection scheme was developed: a MATLAB/Simulink dynamic model emulating a 132 kV transmission line under diverse fault scenarios, and a microcontroller-based hardware prototype employing voltage and current sensors interfaced with an Arduino Uno and GSM module to detect disturbances and transmit location data; experimental validation involved controlled fault injection, waveform inspection, and fault distance estimation via zero-sequence current and voltage dip analysis. Key findings show high-precision fault location with estimation errors consistently below 0.75% over a 30–300 km range, alongside fast response, accuracy, and cost-effectiveness. The study concludes that the combined software–hardware architecture reliably detects and locates SLG faults. The contribution and implication are a scalable, low-cost approach to reducing fault-related outages and enhancing fault management in transmission networks.